In-Vitro Experimental Study of the Antibacterial Activities of Terminalia Arjuna Bark Extract against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa (Community Based Medical Journal, 2026)
The emergence of multidrug-resistant bacteria has renewed global interest in plant-derived antimicrobials. Terminalia arjuna (Combretaceae) bark, traditionally used for cardiovascular and wound-healing therapies, is reputed to possess antibacterial properties, though systematic evaluation is limited. An in-vitro experimental study was performed in collaboration between the Department of Pharmacology & Therapeutics and Department of Microbiology of Mymensingh Medical College, Bangladesh, between January and December of 2024, to assess and compare the antibacterial activity of aqueous (ATAE) and ethanolic (ETAE) bark extracts of T. arjuna against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Extracts were prepared using maceration and tested by Kirby–Bauer disc diffusion and broth-dilution methods. Gentamicin served as the reference antibiotic. Zones of inhibition (ZOI) and minimum inhibitory concentrations (MICs) were recorded and analyzed. Both extracts exhibited concentration-dependent antibacterial activity. The ethanolic extract produced larger inhibition zones (25, 24, 23 mm for S. aureus, E. coli, P. aeruginosa) than the aqueous extract (23, 22, 23 mm). MICs for ETAE were found 150, 200, and 300 mg/mL respectively, which was lower than that of ATAE (200–300 mg/mL), but higher than that of gentamicin (0.75–1.5 µg/mL). Subculture confirmed complete bacterial inhibition at MIC levels. T. arjuna bark exhibited broad-spectrum antibacterial activity, with ethanolic extract being more potent than aqueous extract. Though less powerful than gentamicin, its reproducible inhibition supports the therapeutic potential of T. arjuna as a natural antimicrobial source. CBMJ 2026 July: Vol. 15 No. 02 P:163-171